Penerapan Teori Pembelajaran Humanistik Bagi Siswa di Era Digital - Ajeng Sarwi Lestari (Pusat Riset dan Inovasi Nasional, 2024)
The development of the digital era has now entered into aspects of modern human life. Digitalization has also entered the world of education. In Indonesia itself, you can also find many teachers who use technology as learning media. There are also many learning models used. One way is to use humanism learning theory. The aim of this research is to find out how students can control themselves in technological developments by using humanism theory. The concept of humanism theory education places more emphasis on an optimistic perspective about human nature rather than viewing humans as humans who do not have any abilities or like blank paper that must be filled. This study uses qualitative techniques by collecting reference sources I from journals on Google Scholar.